Voltage-dependent blockade of normal and mutant muscle sodium channels by benzylalcohol. - Haeseler, G; Mamarvar, M; Bufler, J; Dengler, R; Hecker, H; Aronson, J; Piepenbrock, S; Leuwer, M (2000)
1. We studied the effects of benzylalcohol on heterologously expressed wild type (WT), paramyotonia congenita (R1448H) and hyperkalaemic periodic paralysis (M1360V) mutant alpha-subunits of human skeletal muscle sodium channels. 2. Benzylalcohol blocked rested channels at -150 mV membrane potential, with an ECR(50) of 5.3 mM in wild type, 5.1 mM in R1448H, and 6.2 mM in M1360V. When blockade was assessed at -100 mV, the ECR(50) was reduced in R1448H (2 mM) compared with both wild type (4.3 mM; P<0.01) and M1360V (4.3 mM). 3. Membrane depolarization before the test depolarization significantly promoted benzylalcohol-induced sodium channel blockade. The values of K(D) for the fast-inactivated state derived from benzylalcohol-induced shifts in steady-state availability curves were 0.66 mM in wild type and 0.58 mM in R1448H. In the presence of slow inactivation induced by 2.5 s depolarizing prepulses, the ECI(50) for benzylalcohol-induced current inhibition was 0.59 mM in wild type and 0.53 mM in R1448H. 4. Recovery from fast inactivation was prolonged in the presence of drug in all clones. 5. Benzylalcohol induced significant frequency-dependent block at stimulating frequencies of 10, 50, and 100 Hz in all clones. 6. Our results clearly show that benzylalcohol is an effective blocker of muscle sodium channels in conditions that are associated with membrane depolarization. Mutants that enter voltage-dependent inactivation at more hyperpolarized membrane potentials compared with wild type are more sensitive to inhibitory effects at the normal resting potential.